- - Fornells, Hugo Antonio (Acta Bioethica, 2000)
Domiciliary assistance in the context of Palliative Care demands a coordinated action between the regional health system, hospitalizing institutions and home care team. Basic requisites must be complied with when considering the patient's staying at home, playing a major role in this setting, the family and the social environment. Not only the patient and his/her family are benefited, but also the health system, since high-cost and lengthy hospitalizations -in health institutions best prepared to cure than to take care of patients- are reduced. It has been proved that well-organized and efficient palliative care provides an adequate control of symptoms in terminally ill patients and comfort to their families. Some factors implying an unsatisfactory home health care are described: inappropriate home-hospital transition; insufficient pain and other symptoms relief; poor communication and inadequate family support. Home palliative care turns into practical the frequently theoretical ethical principles of beneficence, non-maleficence, autonomy, justice and equity. The task is by no means simple . Changes in health care policies are proposed and a new attitude and perception on the part of health care professionals is encouraged in terms of recognizing and accepting terminally ill patients' real needs and the incurability of certain diseases.